1985
DOI: 10.1128/mcb.5.10.2653
|View full text |Cite
|
Sign up to set email alerts
|

E1A 13S and 12S mRNA products made in Escherichia coli both function as nucleus-localized transcription activators but do not directly bind DNA.

Abstract: We previously purified and characterized functionally the Escherichia coli-expressed product of the human subgroup C adenovirus E1A 13S mRNA (B. Ferguson, N. Jones, J. Richter, and M. Rosenberg, Science 224:1343-1346, 1984; B. Krippl, B. Ferguson, M. Rosenberg, and H. Westphal, Proc. Natl. Acad. Sci. USA 81:6988-6992, 1984). We have now expressed in E. coli and purified the protein product encoded by the human subgroup C adenovirus E1A 12S mRNA and have compared the functional properties of this protein with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
101
2

Year Published

1987
1987
2003
2003

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 155 publications
(108 citation statements)
references
References 45 publications
5
101
2
Order By: Relevance
“…In most experiments, there was a clear increase of E2 RNA in a d11500 infection compared with that in a dl312 infection. This is consistent with other studies that demonstrated an induction of viral transcription by the 12S ElA product (8,24,52). We conclude that the 12S ElA gene product does possess transcription-inducing activity but that the efficiency of this activity depends on the target gene.…”
Section: Simon Et Al In Preparation)supporting
confidence: 93%
“…In most experiments, there was a clear increase of E2 RNA in a d11500 infection compared with that in a dl312 infection. This is consistent with other studies that demonstrated an induction of viral transcription by the 12S ElA product (8,24,52). We conclude that the 12S ElA gene product does possess transcription-inducing activity but that the efficiency of this activity depends on the target gene.…”
Section: Simon Et Al In Preparation)supporting
confidence: 93%
“…It is very unlikely to act directly because isolated E1A protein lacks the ability to bind to DNA (Ferguson et al 1985). It is more likely that it acts through the cellular transcription factors that interact with the inducible promoters.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, these two regulatory activities of E1A have been shown to be separable, but their mode of action remains unclear. It is very unlikely that either trans-activation or repression is accomplished by sequence-specific binding of E1A protein to cis-acting regulatory elements because purified E1A proteins do not bind directly to DNA (Ferguson et al 1985). In addition, there is only limited sequence homology between various promoters activated by E1A, and, except for the E1B promoter (Wu et al 1987), mutational analysis has not led to the identification of sequences specifically required for E1A action; rather, it appears that it is the same promoter elements that are used both for basal level (uninduced)and E1A-induced transcription (for review, see Berk 1986).…”
mentioning
confidence: 99%
“…A wide variety of both RNA polymerase II and III genes introduced into cells as plasmid DNAs or recombinant Ad is activated by the 13S protein, but in no case is the mechanism of action of the 13S protein clear. No DNA consensus sequence involved in 13S activity has been identified, and the 13S ElA protein is not thought to interact directly with DNA (39). Rather, the 13S protein may stimulate the activity of cellular transcription factors, and the precise nature of the interaction between EMA and such factors may be promoter specific (40,41).…”
Section: Resultsmentioning
confidence: 99%